2019
DOI: 10.3390/geosciences9020095
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen Cycle Dynamics Revealed Through δ18O-NO3− Analysis in California Groundwater

Abstract: Nitrate is a significant water-quality issue in California, the United States as a whole, and the world. Critical to addressing nitrate contamination is understanding the presence and extent of denitrification, and further refining the techniques used to identify nitrate sources. The use and understanding of nitrate isotopic signatures to identify nitrate sources have advanced tremendously; however, knowledge gaps remain concerning specific fractionation pathways and the role of denitrification in altering sou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…This empirical metric, however, demonstrably overlooks substantive isotope effects associated with O-atom incorporation into the NO − 3 molecule during nitrification and isotopic exchange of the nitrite intermediate with water, which otherwise give way to nitrified NO − 3 whose δ 18 O NO 3 value is close to that of ambient water (Sigman et al, 2009;Casciotti et al, 2008;Buchwald and Casciotti, 2010;Snider et al, 2010;Boshers et al, 2019). This consideration explains frequent observations of relatively low δ 18 O NO 3 in some soils and saturated systems, which are not explained by simple fractional contribution of reactants (Hinkle et al, 2008;Xue et al, 2009;Fang et al, 2012;Veale et al, 2019). Thus, we posit that the O isotope composition of the NO − 3 imported into the river with increased discharge, which is typical of that in soils and shallow groundwater, does not strictly indicate that shallow-flow NO − 3 originated from proximate nitrification therein, as generally presumed.…”
Section: Confirmed By O Isotope Ratiosmentioning
confidence: 98%
“…This empirical metric, however, demonstrably overlooks substantive isotope effects associated with O-atom incorporation into the NO − 3 molecule during nitrification and isotopic exchange of the nitrite intermediate with water, which otherwise give way to nitrified NO − 3 whose δ 18 O NO 3 value is close to that of ambient water (Sigman et al, 2009;Casciotti et al, 2008;Buchwald and Casciotti, 2010;Snider et al, 2010;Boshers et al, 2019). This consideration explains frequent observations of relatively low δ 18 O NO 3 in some soils and saturated systems, which are not explained by simple fractional contribution of reactants (Hinkle et al, 2008;Xue et al, 2009;Fang et al, 2012;Veale et al, 2019). Thus, we posit that the O isotope composition of the NO − 3 imported into the river with increased discharge, which is typical of that in soils and shallow groundwater, does not strictly indicate that shallow-flow NO − 3 originated from proximate nitrification therein, as generally presumed.…”
Section: Confirmed By O Isotope Ratiosmentioning
confidence: 98%
“…Further supporting the idea that decreases in δ 15 N-NO 3 − were caused by a source shift rather than fractionation changes in nitrification, the measured δ 18 O-NO 3 − values remained steady during fertilizer signal periods (typically all below 0‰; Figure S1). They were also outside the range expected of nitrification processing in the system (+1.5‰ to +2.6‰) based on the assumption that oxygens from source water (δ 18 O-H 2 O; Figure S3) and atmospheric oxygen (δ 18 O-O 2 ; assumed to be constant at +23.5‰) would be incorporated in a 2:1 ratio during nitrification (Amberger & Schmidt, 1987;Boshers et al, 2019;Snider et al, 2010;Veale et al, 2019). A change in Vadose Zone Journal nitrification fractionation would have shifted the isotopic values of δ 18 O-NO 3 − closer to that of the soil water, but this was not the case.…”
Section: Stable Isotopes Of δ 15 N-no 3 − and Mixing Models Reveal So...mentioning
confidence: 99%
“…Furthermore, nitrogen fractionations are negligible in N-limited systems [60]. With regard to δ 18 O − NO 3 , several isotope studies demonstrated that NO − 3 produced by nitrification obtains two oxygen atoms (O) from water molecules and one O atom from the atmosphere [61,62]. Therefore, the δ 18 O of microbial nitrate can be calculated using Equation (6) if the δ 18 O of water and that of atmospheric O 2 are known.…”
Section: δ 15 N and δ 18 O Fingerprint Of Ammonia In Fertilizer And P...mentioning
confidence: 99%
“…Conversely, Synthetic NO − 3 fertilizer is not produced by this same nitrification reaction. It derives all of its oxygen from atmospheric O 2 ; this results in significantly enriched values of δ 18 O − NO 3 ranging from +17 to +25‰ [62,65]. Thus, δ 18 O − NO 3 values may be effectively used to distinguish between ammonia in fertilizer and precipitation from that of nitrate fertilizer.…”
Section: δ 15 N and δ 18 O Fingerprint Of Ammonia In Fertilizer And P...mentioning
confidence: 99%